(untitled) (Bangladesh Veterinarian, 2010)
The effects of methylene blue, vitamin C, adrenaline and oxytetracycline against sodium nitrite intoxication was studied in Long Evan’s (Rattus norvegicus) rats (n=128) in eight groups (A - H). Except control, intoxication was produced by administering sodium nitrite. Rats were treated with methylene blue (group C), vitamin C (group D), adrenaline (group E) and oxytetracycline (group F), and with vitamin C, adrenaline and oxytetracycline (group G); methylene blue, vitamin C, adrenaline and oxytetracycline (Group H). Rats of group C and group H recovered within 24-72 and 13-40 hours, respectively. Other groups showed severe toxic signs including excitement, restlessness, muscle tremor, anoxia, and coma, followed by death within 60 hours. Total erythrocyte count, total leukocyte count, haemoglobin content and packed cell volume were significantly (p<0.01) reduced, and returned to normal at day 14 after methylene blue treatment. The activities of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) were elevated significantly (p<0.01) in all intoxicated groups and within 14 days ALT values reached normal level after methylene blue administration. DOI: 10.3329/bvet.v25i1.4615 Bangl. vet. 2008. Vol. 25, No. 1, 25-31